Prevalence of cardiometabolic risk factors in adults with obesity - Bim, Ricardo Henrique (2022)
Introduction: the prevalence of cardiometabolic risk factors, especially obesity and dyslipidemia, is quite high in the general population. Objective: to identify the presence of cardiometabolic risk factors in adults with obesity and to compare the indices according to sex, age group and obesity level. Materials and Methods: 96 obese adults participated (23% men and 77% women), aged between 18 and 50 years (36.6±8.8) and body mass index (BMI) between 31.3 and 77, 2 kg/m2 (42.5±6.7). Body weight, height, BMI, waist circumference (WC), blood pressure, fasting blood glucose, HDL cholesterol and triglycerides (TG) were evaluated. Results: It was found that 71.9% of the sample had at least two FRCM, metabolic syndrome was diagnosed in 35.4% of the sample and WC was correlated with higher levels of blood glucose and TG, and lower levels of HDL -ç. Men showed more changes in almost all components compared to women. Older age indicated higher WC indices (p = 0.003), while a higher level of obesity was related to altered blood glucose (p = 0.025) and high WC (p = 0.001). Conclusion: The prevalence of cardiometabolic risk factors and metabolic syndrome in adults with obesity is high, and the factors correlate with each other. The treatment of obesity based on behavioral change, with physical exercise and adequate nutrition, may be important to minimize the presence of these risk factors in this population.